Legal Protection for Buyers for the Purchase of Inheritance Land Which the Master Certificate Has Not Been Split - Suryana, Cece; Marniati, Felicitas Sri; Chandra, Tofik Yanuar (Journal of Legal and Cultural Analytics, 2025)
Land is a significant asset with economic, social, and legal value. This study examines the purchase of inherited land whose parent certificate has not been subdivided and the legal protection available to buyers. The research applies a normative legal method with a qualitative juridical approach, using literature studies, case analysis, and interviews with relevant parties such as land deed officials, notaries, and buyers. The study highlights that such transactions carry legal risks due to unclear object definitions under Article 1320 of the Civil Code. Legal protection for buyers is possible if conducted in good faith, administrative obligations are fulfilled afterward, and officials perform professionally. Proper legal procedures are strongly recommended to ensure legal certainty.